Perbedaan Kemampuan Pemahaman Konsep Matematis Siswa dengan Menggunakan Pendekatan Realistic Mathematics Education dan Pendekatan Problem Solving - Siti Yuaeni Ulfah; kowiyah Kowiyah; Daniel Fernandez (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2018)
This study aimed to know the difference of student mathematical concept understanding ability between the aplication of Realistic Mathematical Education and Problem Solving Approaches. This study was held in Sekolah Dasar Negeri Gedong 01 Jakarta Timur. This study method was quasy experiment witj non-equivalent posttest-only control group design. The population in this study was 60 students. The sampling technique in this study was saturation sampling. This study sample who divided into two groups. One group was 1st experiment group that using realistic mathematical education approach and the other one was 2nd experiment group that using problem solving approch. The data was collected using concept understanding ability test in essay. The data was analyzed using t-test. Based on t-test, is was obtained tcount =6.69 and ttable = 2.00 so H0 was rejected. This study was concluded that there was a difference of student mathematical concept understanding ability between realistic mathematical education and problem solving approaches.